Investigate of the Ability of Cronobacter sakazakii Isolated from Clinical Samples of Children Under Two Years to Induce Swimming, Swarming and Biofilm - Zwein, Luma Abdal Hady; Motlag, Tharieyt Abdulrahman; mousa, Mohamed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The study included 200 samples were collected   from   children  under two   years included (50 samples from each of Cerebrospinal fluid, Blood, Stool and Urine) from, Central Children Hospital and Children's Protections Educational Hospital. Isolates bacterial were obtained cultural, microscopic and biochemical examination and diagnosed to the species by using vitek2 system. The results showed there were contamination in 6.5% of clinical samples. The diagnosed colonies which gave pink color on the MacConkey agar , golden yellow color on the Trypton Soy agar and green color on the Birillent Enterobacter sakazakii agar and gave  a probability of 99% in the vitek 2 and were identified as Cronobacter sakazakii. The identification revealed of thirteen isolates: 6(46.16%) isolated from Cerebrospinal fluid samples, 7(53.84%) isolated from blood samples and not isolated bacteria from stool and urine samples. The results of the investigation of some virulence factors showed that all bacteria isolates were able to swimming with a diameter ranging (1-9 mm) and swarming with a diameter ranging (1-40 mm) and their  ability to biofilm formation  by using three methods. The results show the ability  of  isolates to form biofilm by using  Congo red media  methods where it is 12 (92.30 %) out of 13 isolated bacteria belonging to C. sakazakii  able to form biofilm on the Congo red media  which is 3 (23.07%) were  strong production  biofilm ,   8 (61.53%)  were intermediate  production  biofilm and  1 (7.69% ) were weak  biofilm formation , while the 1 (7.69%)  unable to form biofilm.  Tubes method were all isolates were able to form biofilm, it were found that 3 (23.07%)  isolates strong, and 8 (61.53%) intermediate  and 2( 15.38%)  weak biofilm formation. Microtiter plate method  gave 5 (38.46 %) isolates strong, 6 (46.15%) intermediate and 1 (7.69%) weak biofilm formation.